The mechanisms controlling NK cell autoreactivity in TAP2-deficient patients. - Markel, G; Mussaffi, H; Ling, K; Salio, M; Gadola, S; Steuer, G; Blau, H; Achdout, H; de Miguel, M; Gonen-Gross, T; Hanna, J; Arnon, T; et al. (2004)
The killing of natural killer (NK) cells is regulated by activating and inhibitory NK receptors that recognize mainly class I major histocompatibility complex (MHC) proteins. In transporter associated with antigen processing (TAP2)-deficient patients, killing of autologous cells by NK cells is therefore expected. However, none of the TAP2-deficient patients studied so far have suffered from immediate NK-mediated autoimmune manifestations. We have previously demonstrated the existence of a novel class I MHC-independent inhibitory mechanism of NK cell cytotoxicity mediated by the homophilic carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) interactions. Here, we identified 3 new siblings suffering from TAP2 deficiency. NK cells derived from these patients express unusually high levels of the various killer cell inhibitory receptors (KIRs) and the CEACAM1 protein. Importantly, the patients' NK cells use the CEACAM1 protein to inhibit the killing of tumor and autologous cells. Finally, we show that the function of the main NK lysis receptor, NKp46, is impaired in these patients. These results indicate that NK cells in TAP2-deficient patients have developed unique mechanisms to reduce NK killing activity and to compensate for the lack of class I MHC-mediated inhibition. These mechanisms prevent the attack of self-cells by the autologous NK cells and explain why TAP2-deficient patients do not suffer from autoimmune manifestations in early stages of life.